STUDIES ON LYSOSOMES : IV. Solubilization of Enzymes during Mitochondrial Swelling and Disruption of Lysosomes by Streptolysin S and Other Hemolytic Agents - Keiser, Harold (The Rockefeller University Press, 1964)
Streptolysins S and O from hemolytic streptococci were found to induce mitochondrial swelling and the release of malic dehydrogenase from mitochondria; no other streptococcal products were as active. Mg(++), cyanide, dinitrophenol, bovine serum albumin, and antimycin all inhibited streptolysin-induced mitochondrial swelling; only the latter two agents prevented release of malic dehydrogenase from the particles. The streptolysins also solubilized beta-glucuronidase from the less numerous lysosomes of mitochondrial fractions. Vitamin A induced swelling of mitochondria with release of malic dehydrogenase and, at higher concentrations, release of beta-glucuronidase. In these effects, streptolysin S and vitamin A resembled cysteine and ascorbate, which induced swelling and lysis of mitochondria together with solubilization of enzymes. In contrast, mitochondrial swelling induced by such agents as phosphate, thyroxine, or substrates was not accompanied by release of enzymes. The release of enzymes from particles is suggested as a criterion for distinguishing "lytic" agents from those which induce mitochondrial swelling dependent upon electron transport. It was possible to dissociate effects on mitochondria and lysosomes in these experiments; less streptolysin was necessary to damage lysosomes than mitochondria; the converse was found with vitamin A. Injury to mitochondria resulted from the direct action of these agents, since the lysosomal enzymes released as a consequence of their action were not capable of inducing mitochondrial swelling or release of enzymes under the conditions studied.